Ecofriendly-developed polyacrylic acid-coated magnetic nanoparticles as catalysts in Photo-fenton processes - Sanchez, Laura Mabel (2020)
In this work, iron oxide-based magnetic nanoparticles (MNPs) stabilized by polyacrylic acid (PAA) polymer were prepared and characterized as a continuation of a previous research already reported. MNPs composed by pure magnetite cores having good magnetic properties were developed, thus achieving an improvement in the modified coprecipitation method used. The photocatalytic activity of the nanoparticles towards acid orange 7 (AO7), under both radiation types, UV-Vis and LED-Vis, was tested. Pollutant degradation percentages of 64 and 37 % were obtained by using UV-Vis and LED-Vis radiation, respectively.